Physico-chemical characteristics of some Philippine fruits and vegetables - Reyes, Joyce Catherine N.
Certain constituents in mango, banana, pineapple, and tomato were determined at the unripe, rare-ripe and ripe stages of the fruits to disclose any chemical changes associated with ripening. These similar constituents, i.e., pH, % soluble solids, titratable acidity, reducing sugars, sucrose, total sugars, and pectin were also determined in vegetables at normal harvest. The vegetables analyzed were: snap beans, cucumber, onion and pepper. The pH values and titratable acidity of the fruits ranged from 3.0 to 5.5 and 0.07% respectively and were found to have significant differences at the 5% level among the different stages of maturity. The vegetables had pH values above 4.5 and % tiratable acidity was generally between 0.03% and 0.06%. In all fruit samples analyzed, soluble solids content was found to increase considerably during ripening. A similar trend was observed in the reducing sugar contents of the fruits. The average total sugar content of most the fruits was found to be between 1-3% in the unripe stage and 5-10% in the ripe fruits. In the case of vegetables, the average total sugar content was 1.5-3.5% with the exception of onion which had a total sugar of 30% The results in all cases showed a steady decrease in pectin with significance among the three stages of maturity at the 5% level particularly in papaya and tomato.